2017
DOI: 10.1158/1078-0432.ccr-16-1568
|View full text |Cite
|
Sign up to set email alerts
|

ABBV-399, a c-Met Antibody–Drug Conjugate that Targets Both MET–Amplified and c-Met–Overexpressing Tumors, Irrespective of MET Pathway Dependence

Abstract: Despite the importance of the oncogene in many malignancies, clinical strategies targeting c-Met have benefitted only small subsets of patients with tumors driven by signaling through the c-Met pathway, thereby necessitating selection of patients with amplification and/or c-Met activation most likely to respond. An ADC targeting c-Met could overcome these limitations with potential as a broad-acting therapeutic. ADC ABBV-399 was generated with the c-Met-targeting antibody, ABT-700. Antitumor activity was evalu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
117
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(122 citation statements)
references
References 37 publications
5
117
0
Order By: Relevance
“…Herein, we showed a novel strategy for overcoming AZD9291 resistance, providing the first account of the use of a c‐Met‐targeting ADC rather than a c‐Met‐inhibiting antibody. Based on the distinct antitumor mechanism of the ADC, SHR‐A1403, tumors could be screened for c‐Met expression as a biomarker, and having established c‐Met overexpression, treatment with SHR‐A1403 would be sufficient to overcome drug resistance . Thus, we believe that using a c‐Met ADC such as SHR‐A1403 is a more direct and feasible approach for overcoming resistance to EGFR‐TKI and warrants further clinical development.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Herein, we showed a novel strategy for overcoming AZD9291 resistance, providing the first account of the use of a c‐Met‐targeting ADC rather than a c‐Met‐inhibiting antibody. Based on the distinct antitumor mechanism of the ADC, SHR‐A1403, tumors could be screened for c‐Met expression as a biomarker, and having established c‐Met overexpression, treatment with SHR‐A1403 would be sufficient to overcome drug resistance . Thus, we believe that using a c‐Met ADC such as SHR‐A1403 is a more direct and feasible approach for overcoming resistance to EGFR‐TKI and warrants further clinical development.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the distinct antitumor mechanism of the ADC, SHR-A1403, tumors could be screened for c-Met expression as a biomarker, and having established c-Met overexpression, treatment with SHR-A1403 would be sufficient to overcome drug resistance. 27,33 Thus, we believe that using a c-Met ADC such as SHR-A1403 is a more direct and feasible approach for overcoming resistance to EGFR-TKI and warrants further clinical development. Previous studies have sought to overcome resistance to EGFR inhibitors by combining c-Met inhibitors with EGFR-TKI with the goal of causing resistant cells to become as sensitive to EGFR inhibitors as parental cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study we were not able to conduct c-met protein expression or gene amplification correlative studies due to lack of sufficient tumor tissue. A novel MET targeting antibody targeting both ligand-dependent and –independent MET signaling, ABT-700 was well tolerated in early clinical studies and demonstrated anti-tumor activity in select patients with MET amplified tumors (44). A multitude of small molecule MET inhibitors are also being evaluated in clinical trials in combination with EGFR TKIs, including cabozantinib, crizotinib, volitinib and tivantinib.…”
Section: Discussionmentioning
confidence: 99%
“…It is sponsored by AbbVie and, as with other agents, searches have to use ABBV-399 in the NCT data-tables. A report of early results from the Phase I study suggesting efficacy was published by Wang et al in 2017 [36].

NCT02099058: A Phase I/Ib Study with ABBV-399, an Antibody Drug Conjugate, in Subjects with Advanced Solid Cancer Tumors.

…”
Section: Auristatinsmentioning
confidence: 99%